Pengembangan Usaha Nusa Scent sebagai Inovasi Pengharum Mobil Herbal Aroma Nusantara melalui Pendekatan Analisis SWOT dan BMC: Business Development of Nusa Scent as an Innovative Herbal Nusantara-Aroma Car Freshener through the SWOT Analysis and BMC Approaches - Risma Almaidah; Tiara Septiani Agustin; Kristiana Widiawati; Oktaviani Oktaviani; Zalfa Anindya Putri Alfiyah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study aims to analyze Nusa Scent's business development as an innovative herbal car fragrance made from natural ingredients such as lemongrass and cinnamon, emphasizing environmental sustainability. The research employs a descriptive qualitative approach, drawing on literature reviews, interviews, and direct observations of production, packaging, and marketing processes. The analysis employs SWOT and Business Model Canvas (BMC) to evaluate business development strategies. The results indicate that Nusa Scent has strong potential as an innovative, sustainable car aromatherapy product that supports the Sustainable Development Goals (SDG 3, 8, and 12).